Refining Minyak Pelumas Bekas Dengan Proses Fisika-Kimia - Mukhtar G (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Waste lubricant oil classified as a hazardous and toxic materials (B3) which can caused an environmental pollution. Alternative solutions to solve this problem is recycling by refining with physical and chemical processs. The purpose of this this study is the characteristics of refined oil closed to fresh lubricant oil. This study used waste lubricant oil type of NG Lube-40.The process involves screening, evaporation, addition of acid, sedimentation, variations bleaching at 100 oC, oil and solids is separation and the addition of additive. The characteristics of NG Lube-40 based on ASTM method obtained density (15 °C) is 0,8886 g/cm3 and kinematic viscosity at 40°C and 100 °C are 128,2 and 13,5 cSt. The characteristics of waste lubricant obtained density (15 °C) is 0,8916 g/cm3; viscosity at 40 °C and 100 °C are 135,4 cSt and 14,0 cSt. The best bleaching results using three bleaching media between bentonite, bleaching earth and Calcium Oxide obtained the sample results changes color from black to light brown. By varying the addition of solvent, ratio value between volume of waste lubricant with solvent is 33: 1, obtained density (15 °C) is 0,8895 g/cm3 and kinematic viscosity at 40°C and 100 °C are 112,2 and 12,52 cSt. Mean while ratio value between volume of bleached oil with solvent is 40:1, obtained density (15 °C) is 0,8945 g/cm3 and kinematic viscosity at 40°C and 100 °C are 111,2 and 12,44 cSt. This study is still analysis the refined oil (for ratio value between volume of bleached oil with solvent is 100:1). Conclusion for now is the results of solvent addition with ratio 33:1 is closest to the fresh lubricant oil, but there was a decrease of ignition point from temperature 244 oC to 204 oC.